PENGARUH TERAPI AKTIVITAS KELOMPOK SOSIALISASI TERHADAP KEMAMPUAN SOSIALISASI LANJUT USIA DI POSYANDU LANSIA BERMI WILAYAH BINAAN PUSKESMAS DENGGEN - Sasteri Yuliyanti; Erni Payapo (ProHealth Journal, 2020)
This study aims to determine the effect of therapeutic activities of the socialization group on the ability of older people to socialize in the Posyandu for elderly in Bermi under the guidance of the Denggen Health Center in East Lombok district. The research method used was Pre experimental with one group pretest-posttest research design and using total sampling. The results of this study indicate the mean value of the ability of socialization before given treatment is 11.27% and 29.87% after being given treatment. The results of the paired samples test using the SPSS version 16 test showed a significant value of 0,000 (smaller than the value of α = 0.005) which means that there is an effect of therapeutic activity of the socialization group on the ability to socialize the elderly.